HEALTH SYSTEMS RESEARCH IN PAKISTAN: ISSUES, CHALLENGES AND WAY FORWARD - Shaikh, Babar Tasneem (Journal of Ayub Medical College Abbottabad, 2015)
Since we got the definition of Health Systems by WHO in 2000 as a set of cultural beliefs about health and illness that informs the basis for health seeking and health promoting behaviour, the institutional arrangements within which that behaviour occurs, and the socio-economic, political, and physical context for those beliefs and institution1, it has become imperative to define and understand the notion of Health Systems Research. So a research framework or paradigm which encompasses all the dimensions, dynamics, determinants and drivers of health would be called Health Systems Research.2 The goal of such research would be that all stakeholders, i.e., people, institutions and activities will generate relevant, high quality information and synthesize it into knowledge; and will develop tools to improve health systems to address the burden of disease in a specific context.3 Firstly, as always the dearth of credible and authentic research has emerged as the biggest issue, so has been the case with the health systems research. In addition, there has been a failure to create a critical mass of researchers and a research culture. Consequently, policies and political decision in health have seldom used evidence generated by the minimal research available in the country. Supporting and strengthening of research institutions would have been a desirable approach in order to create think tanks to support and supplement government’s decisions. Secondly, there has never been a consensus on the research priorities and an unknown agenda has driven the research in silos without any coordination, linkages and networking. As a result, the evidence generated has not been instrumental to reduce the disparities in health across the populations. A consensus building therefore is imperative between national and international agenda to decide on objectives of health system research.4 Thirdly, researchers need to be incentivized by recognizing their work, providing them the support and exposure, giving them access to bibliographic services, and a competitive career structure. In the absence of such pre-requisites for health systems research, the research conducted lacks context specificity and generalizability, and therefore remains under-utilized. It is also difficult to compare such research across multiple health systems and its applicability and transferability is quite challenging.2 The biggest question for a health systems researcher is whether to employ health systems research for reducing the burden of disease; for improving population health outcomes, or to strengthen the health system per se. Hitherto, researchers have studied the determinants of health seeking behaviours and health service utilization for informing the policy makers.5 Today, when the global community is contemplating on the sustainable development goals, after having seen the fate of the millennium development goals, there is an even greater need for the health systems research to understand the complexities and intricacies involved in improving the performance of the health system. Epidemiological studies and Population based studies need to be reconciled to understand the disease phenomenon; yet these have their entrenched limitations to guide toward the system’s improvement.6 A pragmatic way forward would be to conduct health system research in order to create an evidence and information base for policy formation, which is the foremost step toward improving the health system. The urgent need in Pakistan’s context is to advocate for increased resources for health sector, realizing the need, priority and the population pressure. Moreover, enabling improved resource allocation among competing priorities within health system research is also worth looking at. In this regard, WHO’s health system strengthening building blocks give us a starting point for improving health systems performance.7 An institutional change necessitates a deeper study of the social and cultural factors embedded in our health system.8 We know that health status depends on many determinants; and with unlimited resources, we could act on all of them. Nonetheless, with resources being limited, we have to select the determinants which have the greatest impact on health. Only through health systems research, a country can identify the key determinants for the health of the country. However, the conditions of success would be to keep research out of isolation, disseminate, and try to get it translated into actions. Henceforth, a research which can look into all important pillars of governance, service delivery, supplies and technology, human resources, financing, and information system could be a turning point for bringing about a sustainable and meaningful change in the fragile health system of this country.